2000
DOI: 10.1002/aic.690461015
|View full text |Cite
|
Sign up to set email alerts
|

Engineering approximations for activation energies in hydrogen transfer reactions

Abstract: Pre®ious in®estigators ha®e often used the Polanyi relationship, extensions due to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 35 publications
2
84
0
1
Order By: Relevance
“…By using Equation (10), tunneling coefficients for hydrogen abstraction reactions of the CÀHÀ-C type involving hydrocar- CHEMPHYSCHEM ARTICLES www.chemphyschem.org bons and organosulfur compounds could be reproduced in the temperature range from 300 to 1500 K within a factor of 1.15. The validity of Equation (10) for hydrogen abstraction reactions involving S-centered radicals will be assessed in this work.…”
Section: Tunnelingmentioning
confidence: 99%
“…By using Equation (10), tunneling coefficients for hydrogen abstraction reactions of the CÀHÀ-C type involving hydrocar- CHEMPHYSCHEM ARTICLES www.chemphyschem.org bons and organosulfur compounds could be reproduced in the temperature range from 300 to 1500 K within a factor of 1.15. The validity of Equation (10) for hydrogen abstraction reactions involving S-centered radicals will be assessed in this work.…”
Section: Tunnelingmentioning
confidence: 99%
“…Other and more accurate relations have been proposed based on Bond Order and on Valence Bond theory (Donahue et al, 1998;Zavitsas, 1998;Clarke et al, 2000;Blowers and Masel, 2000;Fischer and Radom, 2001;Shaik et al, 2001). The second category is related to Benson's group additivity method for thermodynamic data.…”
Section: Introductionmentioning
confidence: 97%
“…The ever-increasing computational power and the development of better algorithms bring the accurate calculation of kinetic and thermodynamic parameters for industrially relevant gas-phase reactions from first principles within reach. Hydrocarbon free-radical reactivity and thermochemistry have been studied with a variety of computational methods, ranging from semiempirical to density functional theory (DFT) and postHartree-Fock methods (Wong et al, 1994;Barone and Orlandini, 1995;Heuts et al, 1996;Xiao et al, 1997;Wong and Radom, 1998;Blowers and Masel, 2000;Chuang et al, 2000;Stahl et al, 2001;Sumathi et al, 2001aSumathi et al, ,b, 2002. It is found that in order to obtain results with so-called chemical accuracy for standard enthalpies of formation, that is, better than 4 kJ/mol, calculations on radical species and on radical reactions require large basis set post-Hartree-Fock methods (Mayer et al, 1998;Chuang et al, 2000;Saeys et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a variety of methods for rate prediction of radical reactions has been developed. These methods range from correlating the activation energy to the reaction enthalpy, such as Evans-Polanyi correlations and its variations, [15][16][17] to more sophisticated methods based on the structure of the transition state. Several of the latter methods are related to Benson group 2 additivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a variety of methods for rate prediction of radical reactions has been developed. These methods range from correlating the activation energy to the reaction enthalpy, such as Evans-Polanyi correlations and its variations, [15][16][17] Sabbe et al ChemPhysChem 11:195-210 (2010) -pre-reviewed version 2 additivity. [18,19] Among these are: 1. the structural group contribution method of Willems and Froment, [20,21] in which correction terms on the Arrhenius parameters of a reference reaction account for structural differences between the latter and the considered reaction; 2. methods that calculate the thermochemistry of the transition state, such as the method described by Sumathi et al, [22][23][24] 3. the Reaction Class Transition State Theory developed by Truong et al [25,26] and 4. the group additive (GA) method for activation energies as described by Saeys et al [27,28] Experimental determination of all the kinetic and thermodynamic parameters required for these methods is not possible due to scarcity of experimental data.…”
mentioning
confidence: 99%